Comparative Analysis of Data Analysis and Probability Topics between IB and Non-IB Mathematics Textbooks - Birgili, Bengi; Saralar-Aras, İpek (Journal of Instructional Mathematics, 2024)
It is imperative to explore the organization of contemporary teaching and learning methods in data analysis and probability within mathematics curricula, with a specific focus on comparing non-IB and IB approaches. This study analyzed how the contemporary teaching and learning of data analysis and probability was organized through an analysis of two textbooks as an intended mathematics curriculum (non-IB and IB respectively) by discussing similarities and differences between the two. It employed content analysis method to examine structural features, technology usage, and real-life connections by focusing on the topic in depth, exploring content, organization, and representation. This study results disclosed that both open-ended and closed-ended item formats were recommended, without clear superiority. Descriptive examples and percentages were provided to guide curriculum developers and support teachers in enhancing student learning outcomes. The study hopes to assist middle school students in achieving higher scores in international assessments such as PISA and TIMSS. It emphasizes the potential for revising mathematics curricula and textbooks to better meet students' needs, drawing inspiration from the success of the IB program.